Development and delivery of biofortified crops at scale. Project profile. - International Potato Center (International Potato Center, 2019)
Building on the success of the International Potato Center’s (CIP) nutritious sweetpotato program, vitamin A-rich orange-fleshed sweetpotato will improve the diets of millions more households in Africa and Asia through a program to scale up biofortification.